(untitled) (Computer systems and information technologies, 2025)
In the modern world, blockchain technologies are gaining popularity due to their ability to ensure security, transparency and decentralization of data. One of the most promising platforms is The Open Network (TON), which provides unique opportunities for the development of smart contracts. This article discusses the main features of the TON blockchain and its advantages in the context of educational process automation. Smart contracts implemented on the TON platform can serve as a tool for optimizing educational systems. They allow to automate processes related to knowledge validation, grade management, and even finance in educational institutions. For example, smart contracts can provide automatic scholarships based on students’ grades, as well as control over the implementation of curricula. The paper also analyzes the benefits of using smart contracts in the educational process, such as reducing administrative costs, increasing transparency, and reducing fraud risks. In addition, blockchain technologies provide an opportunity to create decentralized platforms for storing and sharing knowledge, which makes learning more accessible and effective. Particular attention is paid to the mathematical aspects that ensure the functioning of TON, as well as sharing mechanisms that allow the platform to process thousands of transactions per second. These technologies can be used to create educational applications requiring high bandwidth and data processing speed. The paper contains formulas that illustrate the technical characteristics of the TON blockchain and provides a detailed analysis of its architecture. The study shows that smart contracts on the TON platform have the potential to revolutionize educational processes by providing new tools for data management and security.